Health is putting oneself at risk: vital normativity in Georges Canguilhem - Neves, Tiago Iwasawa; Porcaro, Luiza Almeida; Curvo, Daniel Rangel (Saúde e Sociedade, 2017)
This article aims to criticize the biomedical health model prevalent in medical sciences, based on the concept of vital normativity proposed by Georges Canguilhem. In the introduction we present, from a brief history of the health concept, normalization as the fundamental primacy of the biomedical model. In the first part, we discuss the problem of determining normal and pathological, health and illness in Canguilhem’s thought, seeking to situate these concepts in function of individual values, questioning the existence of a normative process in Biology. In the second part, it aims to demonstrate that the vital normativity advocated by Canguilhem is a fundamental conceptual tool for the understanding of organic production logic. This production logic in Biology does not take the norm as criterion for valuing possible forms of life. Biological individuals do not fit or deviate from the rules, but biological individuality, as a power of generating new ways, produces the normativity process. Finally, we highlight the critical impact of the concept of health understood as an openness to risk, emphasizing this dimension of health as capacity to face new situations of life.